Treatment of chronic colorectal fistula with the over-the-scope-clipping system: a case report - Aliosinas, Olegas; Radziunas, Gintautas; Dulskas, Audrius; Samalavicius, Narimantas E. (Lietuvos chirurgija, 2015)
Anastomotic leakage in colorectal surgery is an infrequent but in some cases very serious or even lethal complication. The over-the-scope-clipping (OTSC) system (Ovesco), which was originally developed to treat intestinal perforation and was tested on animals, could be the answer for the patient with such situation. We present a case of 63-year-old man suturae insuffitiency at the 40th post-operative day. The conservative treatment was long and unsuccessful. The lesion was then closed with two subsequent clips, and the patient recovered well without major interventions. The lesion showed a normal healing on the follow-up.